2016
DOI: 10.1007/s00240-016-0954-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is prevalent among idiopathic stone formers, but does correction pose any risk?

Abstract: While vitamin D (vitD) deficiency is thought to contribute to poor health in a variety of ways and should be corrected, there is still concern about giving vitD supplements to patients with a history of nephrolithiasis. The aim is to study the prevalence of vitD deficiency and the effect on stone risk of cholecalciferol (vitD3) supplementation in a cohort of idiopathic stone formers (ISF). We screened for vitD deficiency and urinary measures of stone risk, comparing vitD deficient (serum 25-OH vitD ≤30 nmol/L;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…Since vitamin D may increase kidney stone formation through an increase in urine calcium excretion, the evaluation of urinary calcium excretion after vitamin D supplementation is a major concern. Only two studies investigated the effect of nutritional vitamin D on urinary calcium excretion on a prospective basis [ 70 , 71 ]. Leaf et al prescribed ergocalciferol to 29 stone formers with relatively low 25-hydroxyvitamin D serum levels at baseline and concluded that a limited course of vitamin D repletion does not aggravate the mean urinary calcium excretion, although a subset of individuals may have an increase [ 70 ].…”
Section: Interventional Studiesmentioning
confidence: 99%
“…Since vitamin D may increase kidney stone formation through an increase in urine calcium excretion, the evaluation of urinary calcium excretion after vitamin D supplementation is a major concern. Only two studies investigated the effect of nutritional vitamin D on urinary calcium excretion on a prospective basis [ 70 , 71 ]. Leaf et al prescribed ergocalciferol to 29 stone formers with relatively low 25-hydroxyvitamin D serum levels at baseline and concluded that a limited course of vitamin D repletion does not aggravate the mean urinary calcium excretion, although a subset of individuals may have an increase [ 70 ].…”
Section: Interventional Studiesmentioning
confidence: 99%
“…However, a recent small RCT comparing 6 weeks of low (1 000 IU/day) versus high (50 000 IU weekly) dose vitamin D supplementation among 21 vitamin D deficient stone formers found no significant change in urinary calcium after treatment in either group, although only the higher dose group showed a significant increase in serum vitamin D levels [51] . If vitamin D repletion is indicated, urine calcium should be monitored with 24 h urine studies [52] , [53] .…”
Section: Dietary Managementmentioning
confidence: 99%
“…Although Reid and colleagues’ study challenged the role of vitamin D supplementation in improving bone mineral density [58,59], supplementation of vitamin D has many beneficial effects [60,61,62,63]. However, many doctors and patients are concerned about whether vitamin D repletion will increase the risk of urolithiasis, especially in SFs [64]. A recent systematic review and meta-analysis demonstrated that long-term vitamin D supplementation resulted in increased risks of hypercalcemia and hypercalciuria, but did not increase risk of kidney stones [55].…”
Section: Discussionmentioning
confidence: 99%